HEALTH PROFILE IN THE FIRST THOUSAND DAYS OF CHILDREN ACCOMPANIED IN SECONDARY HEALTH CARE (Movimenta (ISSN 1984-4298), 2021)
Introduction: The WHO recommends that care during pregnancy, childbirth and in the first years of life is essential for a healthy life in the future. Prematurity can have an impact on child development and Brazil is one of the 10 countries responsible for more than 60% of premature births worldwide. Another factor that should be a reason for surveillance and care are congenital syndromes, especially STORCH syndromes, which can be acquired intrauterine, during childbirth or in the postpartum period and constitute a considerable public health problem worldwide. Objective: To characterize the health profile of children between 0 and 3 years old of the Municipal Health Assistance Network in a city in the south of the country. Method: Cross-sectional, retrospective study, based on analysis of medical records of children discharged from a public Neonatal Intensive Care Unit, followed up in Secondary Health Care in the city of São Leopoldo, RS. Results: The sample consisted of 300 records, and the data were stratified by risk factors STORCH and prematurity. 107 cases of congenital infections (35.7%) and 111 cases of preterm birth (37%) were identified, which presented more complications in the prenatal period (27%). Congenital syphilis infection was the most prevalent in both groups (83.2% in STORCH and 9.9% in preterm). Conclusion: The findings reveal the need for strategies for access to health services, seeking the quality of care and monitoring of children included in the Health Care Network, in order to avoid overloading the public system.
Keywords: Premature. Syphilis, Congenital. Health Profile.